Efficient generation of an array of single silicon-vacancy defects in silicon carbide - Wang, Junfeng (2018)
Color centers in silicon carbide have increasingly attracted attention in recent years owing to their excellent properties such as single-photon emission, good photostability, and long spin-coherence time even at room temperature. As compared to diamond, which is widely used for hosting nitrogen-vacancy centers, silicon carbide has an advantage in terms of large-scale, high-quality, and low-cost growth, as well as an advanced fabrication technique in optoelectronics, leading to prospects for large-scale quantum engineering. In this paper, we report an experimental demonstration of the generation of a single-photon-emitter array through ion implantation. VSi defects are generated in predetermined locations with high generation efficiency (approximately 19%±4%). The single emitter probability reaches approximately 34%±4% when the ion-implantation dose is properly set. This method serves as a critical step in integrating single VSi defect emitters with photonic structures, which, in turn, can improve the emission and collection efficiency of VSi defects when they are used in a spin photonic quantum network. On the other hand, the defects are shallow, and they are generated about 40 nm below the surface which can serve as a critical resource in quantum-sensing applications.